Online Learning Analysis of Education Statistics Department of Tadris Biology Faculty of Tarbiyah & Teaching Science UIN-SU Medan - Wahyuda, Agus; Putri, Ananda; Humairoh, Siti; Ramadana, Azzahra Putri; Rahayu, Reni; Daulay, Rabiah Afifah (META: Journal of Science and Technological Education, 2022)
During the Covid-19 pandemic, online learning is a solution in the world of education, including learning carried out by Tadris Biology students at UIN North Sumatra. This research focuses on education statistics courses conducted online. The data collection technique was carried out through a google form questionnaire and followed by a qualitative descriptive analysis. The research subjects were Biology Tadris students who were in the Even Semester of the 2022-2023 Academic Year who took education statistics courses with a total of 86 students as respondents. The purpose of this study was to determine the level of success in online learning of educational statistics. The results of student responses stated that online learning of educational statistics was not going well in terms of psychology and facilities, but in terms of educators (lecturers) it was good in online lectures with WhatsApp as a learning medium that was often used.